2014
DOI: 10.1117/12.2041609
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a multimodal CT-video chest model

Abstract: Bronchoscopy enables a number of minimally invasive chest procedures for diseases such as lung cancer and asthma. For example, using the bronchoscope's continuous video stream as a guide, a physician can navigate through the lung airways to examine general airway health, collect tissue samples, or administer a disease treatment. In addition, physicians can now use new image-guided intervention (IGI) systems, which draw upon both three-dimensional (3D) multi-detector computed tomography (MDCT) chest scans and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…In prior work, we presented the concept of a multi-modal CT-video chest model which fuses summarized endobronchial video sequences with a CT-derived airway-tree model. 4 This effort depended on manually selected key frames and reported an average reduction of example video sequences of 65%. Our current method represents a major step forward from our earlier work toward a fully automatic method for fusing endobronchial video with a CT-derived airway-tree model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior work, we presented the concept of a multi-modal CT-video chest model which fuses summarized endobronchial video sequences with a CT-derived airway-tree model. 4 This effort depended on manually selected key frames and reported an average reduction of example video sequences of 65%. Our current method represents a major step forward from our earlier work toward a fully automatic method for fusing endobronchial video with a CT-derived airway-tree model.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, based on the condition number of H, if the number of quality feature matches between the two frames is sufficient, then we consider the frames to be matched and add the latter frame to current shot S i . 4 Otherwise, subsequent frames are compared against the current frame until a search neighborhood range is exceeded. This process continues for a new shot, with S i+1 initialized with the frame following the last frame of S i .…”
Section: Endoscopic-shot Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rather than using the time consuming pixel-wise similarity measures, more efficient registration approaches based on airway lumen feature matching have been proposed in [17][16][4] to perform realtime bronchoscopic localisation. In addition, a feature-based visual SLAM [18] is also investigated for localisation in the endobronchial environment. However, the visual odometry approach is prone to insufficient visual features such as SIFT or ORB for tracking.…”
Section: A Geometry-based Localisationmentioning
confidence: 99%
“…Recent clinical studies of high-resolution fiber-optic microendoscopy have demonstrated that this method can be used to detect neoplastic lesions in patients with oral squamous cell carcinoma 6 and Barrett's esophagus. Automated frame selection algorithms and procedures have been reported for laparoscopic videos, 9 colonoscopy videos, 10 capsule endoscopy videos, [11][12][13][14][15] cystoscopy videos, 16 angiography videos, 17 bronchoscopic videos, 18 larynx endoscopy videos, 19 and retinal videos. The field of view is typically 0.5 to 1.0 mm in diameter with a lateral resolution of about 4 μm.…”
Section: Introductionmentioning
confidence: 99%